Fractal Control Theory - Liu, Shu-Tang.; Wang, Pei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on the control of fractal behaviors in nonlinear dynamics systems, addressing both the principles and purposes of control. For fractals in different systems, it presents revealing studies on the theory and applications of control, reflecting a spectrum of different control methods used with engineering technology. As such, it will benefit researchers, engineers, and graduate students in fields of fractals, chaos, engineering, etc.
Introduction -- Fractal Control of Planar Complex Dynamical Systems -- Synchronization of Julia Sets -- Identification Control for Julia Sets -- Fractal Surface and Control of Fractal Surface -- Control and Synchronization of Spatial Julia Sets -- Control of Julia Sets in Complex Henon Systems -- Control of Rational Fractal Sets -- Control and Application of Fractal Growth -- Control on Julia Sets in Switching Complex System.
Keywords: Dynamics; Nonlinear theories; Control engineering; Nonlinear Optics; Applied Dynamical Systems; Control and Systems Theory; Nonlinear Optics